KAJIAN LITERATUR SISTEMATIS MODEL TINGKAT KEMATANGAN BUDAYA KESELAMATAN (SAFETY CULTURE MATURITY MODEL) DI BERBAGAI SEKTOR INDUSTRI - SISTEMATIK REVIEW - Hamas Musyaddad Abdul Aziz; Zulkifli Djunaidi (Universitas Pahlawan, 2022)
The importance of assessing the maturity level of safety culture has been a concern in various industrial sectors and studied by many researchers. Frameworks for measuring safety culture maturity have been developed and varied. The purpose of this study is to review the basic and conceptual development of safety culture maturity levels from various industrial sectors, as well as provide an overview of information on how the development model is used. This study is a systematic review using the Preferred Reporting Items for Systematic Reviews & Meta Analysis (PRISMA) method. The databases used in searching the data are Science Direct, PubMed and Google Scholar. The keywords used are safety culture maturity, safety culture maturity model, and safety maturity level by producing articles that are relevant to the purpose of the literature study as many as 23 publications were reviewed. Based on the results of the literature review, the methods used in developing, evaluating and implementing safety culture maturity levels are literature review, interviews, matrices, expert or expert consultation, Focus Group Discussion (FGD), questionnaires, audit documents, score cards or assessments, accident data. , and some are not reported. Most of the publications in the review sample were included in developments whose main objective was to build a model of the maturity level of safety culture in each industrial sector application. This systematic review found that the analysis of the maturity assessment identified the level of safety culture maturity that varied with each model development. Keywords : Safety culture , Maturity model, Industry